Procedimento alternativo de preparação de carbonato de cálcio precipitado de elevada pureza - Sobral, Francisca Eliene (1995)
This work presents a method for preparing Precipitated Calcium Carbonate based on Calcium Oxide dissolution in aqueous solution of Monoethanolamine Hydrochloride, followed, by Calcium Carbonate Precipitation after carbonation with Carbon Dioxide of the resulting solution. This method allows the use of any limestone raw material, independent of the initial composition, always resulting in high purity final product. The method consists of two steps: the reaction of Calcium Oxide dissolution in a Monoethanolamine Hydrochloride solution and the Calcium Carbonate precipitation by carbonating the resulting solution from the first step using Carbon Dioxide. Looking for optimized yelds, for both steps, the following parameters variation were studied: concentration of reagents, molar rate of reagents, reaction temperature and time length. Also, a study was performed in order to obtain the data on the mass balance of the preparative cycle involving recycling of the Monoethanolamine Hidrochloride solution regenerated at the end of the second step. The present method was applied to a sample of quicklime from CARBOMIL QUÍMICA S/A (Limoeiro do Norte, Ce), in order to obtain information on the quality of the final product from that raw material. The synthetic Calcium Carbonate obtained was characterized by atomic absorption spectrophotometry for determining trace elements (Al, Cu, Fe, Mg, Mn e Na) and by X-ray diffractometry (powder method) to identify the different crystalline phases (Aragonite, Calcite and Vaterite) present.